Beliefs about animal emotions are associated with self-reported consumer behaviors related to animal use - Michael A. Kisley (PLoS ONE, 2026)
Human-held beliefs about the emotional capacity and experience of non-human animals appear to be related to attitudes concerning animal use, but direct links between such beliefs and consumer behaviors that affect animals have not been investigated. Two survey-based studies were conducted to test whether scores on the Beliefs about Animal Emotions Scale (BAES) are associated with self-reported consumer behaviors. In Study 1, beliefs about animal emotions statistically predicted reported frequency of non-dietary animal use avoidances (e.g., avoiding animal-tested products, animal-based competitions), over and above age, gender, and educational attainment in a U.S.-based sample. Study 2, which involved targeted recruitment of self-identified vegetarians and vegans, largely replicated these findings, and further showed that BAES scores predicted the number of reported animal-product food avoidances. Having established a link between beliefs about animal emotions and animal-related behavioral choices, additional analyses were conducted to investigate potential factors that contribute to such beliefs. Educational attainment was a consistent negative predictor of BAES scores across both studies: more highly educated participants attributed less emotional capacity and experience to animals. Exploratory analyses indicated that, based on self-report, there are numerous sources of information that contribute to beliefs about animal emotions including, most notably, direct interaction with pets and personal belief systems (e.g., moral, spiritual). Together, these results indicate that individual differences in beliefs about animal emotions, in particular beliefs concerning emotional complexity and authenticity, as well as beliefs about the moral relevance of animal emotions, are importantly related to self-reported consumer behaviors that have implications for animals.